Ustavno sodišče med negativno in pozitivno selekcijo zadev - Ribičič, Ciril (Podjetje in delo, 2024)
The author examines the changes to the Constitution regarding the Constitutional Court, mainly from the point of view of the positive selection of constitutional initiatives and appeals. In doing so, he rejects the assessments that this will prevent individuals from accessing the Constitutional Court. Even less convincing is the claim that the purpose of the changes is to ensure the satisfaction of constitutional judges. On the basis of positive selection, the most important cases for the complainants and for the development of the rights protection system will be selected, which will require more in-depth consideration. In his opinion, the circle of authorised proposers should be narrowed. He advocates for the President of the Republic to be given the right to a preliminary request for an assessment of the constitutionality of the adopted law, which they considers inconsistent with the Constitution.